Literature Review of the Influence of Tax Dissemination, Tax Sanctions and Taxs System on Individual Taxpayer Compliance (Empirical Studyion Taxpayersiin East Jakarta) - Juhdi Ropiki; Tutty Nuryati; Uswatun Khasanah (Peneliti.net, 2023)
Taxes are the prima donna of Indonesia's income, where the donated taxes are almost 80%. Previous research or relevant research serves to strengthen the theory and phenomenon of the relationship or influence between variables. This article reviews taxpayer compliance that is influenced by tax socialization, tax sanctions, and the tax system. The purpose of writing this article is to build a hypothesis on the influence between variables for use in further research. The results of this literature review article are: 1) Socialization of taxation affects taxpayer compliance, 2) Tax Sanctions affect taxpayer compliance, 3) Taxation System affects taxpayer compliance, and 4) Socialization of taxation, Tax Sanctions, and Taxation Systems have an effect simultaneously on taxpayer compliance.